PENGEMBANGAN BAHAN AJAR MATA KULIAH FISIOLOGI REPRODUKSI DI JURUSAN BIOLOGI UNIVERSITAS NEGERI MALANG - Irmawati, Farizha; Lestari, Umie; Suwono, Hadi (Jurnal Florea, 2015)
The purpose of the research and development is to produce teaching materials such as textbooks supporting course in Reproduction Physiology research based on the toxicity analysis for students whotake a course in Reproduction Physiology. This research is a research and development, where theresults of research become the teaching materials developed supporting Reproduction Physiologycourse. Development models have prepared using ADDIE Model. Sources of data in this researchinclude laboratory research and validation of the results sheet of Biotechnology material experts,instructional design experts, the media, and the trials in students. The analysis is used quantitative andqualitative.The results of the research have developed become teaching materials like text bookssupporting courses and have been validated by the Reproduction Physiology, the ReproductionPhysiology material experts, instructional design experts, the media, the individual testing, and grouptrials. Based on the results of the validation material have obtained value of 95%, the results of thedesign validation and media experts to get the value of 93.75%, it means that the teaching materials hasbeen developed which suitable to be used as a teaching material support biotechnology course. Whilethe experiments performed to get a data the percentage of students that are equal to 88,25 % andincluded in the category of âvery goodâ, but still need to be revised based on advices and commentsfrom students.Keywords: Development, Instructional Material, ADDIE